Engineering language education in the 21st century: consistency of language nationalism and the construction of new Malay culture - Mohd. Hanapi, Noor Azura; Abd. Rahman, Fadzilah (Universiti Sultan Azlan Shah, 2022)
The Malay language is a language that is able to translate many fields of knowledge like, Mathematics, Science, Engineering, Religion, Technology, Civilization, and others. The ability of the Malay language to serve as the language medium and official language of nations in the Malay Archipelago is beyond doubt. The ability of the Malay language based on its use, its flexibility, and the capacity of its speakers has enabled it to stand on par with other world languages through technological developments in the field of communication. This paper discusses the progress in the teaching of the Malay language in the 21st century and the working mechanism of teaching Malay that has undergone a revolution in the context of language nationalism, as well as the consistency of the ethnic Malay culture resulting from the explosion of the 21st century and the world of Information and Communications Technology. This revolution has changed the ways the Malays look at their own language and culture. The relationship between language and culture as the source of the Malay identity will be discussed in relation to the consistency of language nationalism and the development of the Malay culture in line with the development of technology without trivializing the Malay language itslef.